Molecular Docking and Molecular Dynamic Simulation of 1,5-Benzothiazepine Chalcone Derivative Compounds as Potential Inhibitors for Zika Virus Helicase - Frimayanti, Neni; Nasution, Musyirna Rahmah; Etavianti, Elsa (Jurnal Riset Kimia, 2021)
Zika virus caused of the emerging infections characterized by fever, Guillain-BarrÃ© syndrome (GBS) for adults. In the current work, we aimed to study the binding orientation of 1,5-benzothiazepine compounds as new potential agent against Zika virus inhibitor through molecular docking and molecular dynamic simulation. Since, 1-5-Benzothiazepines are particular interest for drug discovery and they also has some biological activities. However, their antiviral activities and in silico studies of the binding to their biological targets have not been extensively investigated. Molecular docking study of 1,5-benzothiazepine chalcone derivatives compounds with protein target 5GJB (PDB ID) and this protein was taken from the crystallographic structure. In this study, twelve 1,5-benzothiazepine chalcone derivative compounds were docked to the protein with the grid box along x, y and z radius of 26.85, 28.17 and 24.43 Ã…, respectively. Suramin was used as positive control. Thus, it can be used as a reference for design new inhibitors for Zika virus helicase. Based on the docking results, it is observed that compounds MA3 and MA8 are estimated to have activity as inhibitors for Zika virus helicase with binding free energy values of -4.6490 and -4.9291 kcal/mol, respectively. MA3 and MA8 were also stable during the MD simulations with the hydrogen bonding are still maintained before and after MD simulation. Furthermore, both of these compounds can be used an early stage for drug design and drug delivery process.